Aproximación al Teatro Musical Desde el Canto y la Danza (2021)
The musical is a broad genre, which offers the artist multiple interpretive possibilities in where theater, song and dance are its main components, demanding from the artist a interdisciplinary training that expands their creative and interpretive capacities. This stimulates my need from the song, investigate this genre and delve into the interrelation of the disciplines that according to this apparently unknown genre and with little presence on stage and national repertoires. Almazán (2015) tells us “musical theater allows the artist to cultivate values, attitudes and habits linked to coexistence and teamwork, as well as to the processes that it entails taking risks and solving problems creatively” (p. 7,8). In this sense of the quote, I consider essential a comprehensive training that allows me as artist, to have tools that strengthen my research and creation processes that can replicated in the future, understanding that artistic training requires permanent work. In addition, this is developed as a team exchanging knowledge and experiences, where taking risks is part of the approach to an artistic project. For me the dance in the interpretation musical and dramatic is a fundamental communicative fact to be able to transmit feelings and visual and auditory emotions.